Hubble Space Telescope STIS Observations of the Wolf-Rayet star HD 5980 in the Small Magellanic Cloud : II. The Interstellar Medium Components - Koenigsberger, Gloria (2001)
Observations of the interstellar and circumstellar absorption components obtained with the Hubble Space Telescope Space Telescope Imaging Spectrograph (STIS) along the line of sight toward the Wolf- Rayet-luminous blue variable (LBV) system HD 5980 in the Small Magellanic Cloud are analyzed.